Pengaruh Rasio Likuiditas, Leverage, Dan Profitabilitas Terhadap Financial Resilience Pada Industri Food And Beverage (F&B) Dalam Masa Krisis Ekonomi - Ari Setyo Wati; Mayrilin Kayla Dedyanti; Nabilah Febriyanti; Maria Yovita R Pandin (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the financial performance of financial resilience in times of crisis of each company engaged in the Food and Beverage (F&B) sector, namely PT Indofood Sukses Makmur Tbk, PT Unilever Indonesia Tbk, and PT Sentra Food Indonesia Tbk during 2019- 2021 through ratio analysis. The data analysis method used is a quantitative descriptive method, namely by collecting, processing, and interpreting the data obtained so that it can provide a clear picture of the situation under study based on the numbers. The result of this study is that the liquidity ratio has a significantly positive effect on financial resilience. While the leverage ratio and profitability ratios have no significant positive effect on financial resilience.